2016
DOI: 10.1093/brain/awv383
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-132 and early growth response-1 in nucleus basalis of Meynert during the course of Alzheimer’s disease

Abstract: The cholinergic nucleus basalis of Meynert, which is important for memory functions, shows neuronal activation ('up-phase') during the early stages of Alzheimer's disease and neurodegeneration ('down-phase') in later stages of Alzheimer's disease. MicroRNA-132 (miR-132) and the transcription factor early growth response-1 (EGR1) were proposed as possible candidate molecules regulating such an up-down activity pattern of the nucleus basalis of Meynert during the course of Alzheimer's disease, as they both show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 56 publications
7
49
0
Order By: Relevance
“…Distinct technological platforms, different tissue repositories, variable postmortem interval to sample storage, divergent processing protocols, and inadequate sample size may all introduce bias into the publically available datasets. Nevertheless, miR-132 deficiency has been consistently reported in the context of neurodegeneration (13), supporting the significance of miR-132 in the pathogenic processes of sporadic, lateonset AD (6)(7)(8)(9)(10)(11)(12), PD (14), HD (15), ALS (16), frontotemporal lobar degeneration with TAR DNA-binding protein 43 (TDP) inclusions (17), Pick's disease, progressive supranuclear palsy (PSP) (8), prion diseases (18), and spinal muscular atrophy (SMA; summarized in Table 1).…”
Section: Mir-132 Deficiency In Ad and Other Neurodegenerative Diseasesmentioning
confidence: 81%
See 2 more Smart Citations
“…Distinct technological platforms, different tissue repositories, variable postmortem interval to sample storage, divergent processing protocols, and inadequate sample size may all introduce bias into the publically available datasets. Nevertheless, miR-132 deficiency has been consistently reported in the context of neurodegeneration (13), supporting the significance of miR-132 in the pathogenic processes of sporadic, lateonset AD (6)(7)(8)(9)(10)(11)(12), PD (14), HD (15), ALS (16), frontotemporal lobar degeneration with TAR DNA-binding protein 43 (TDP) inclusions (17), Pick's disease, progressive supranuclear palsy (PSP) (8), prion diseases (18), and spinal muscular atrophy (SMA; summarized in Table 1).…”
Section: Mir-132 Deficiency In Ad and Other Neurodegenerative Diseasesmentioning
confidence: 81%
“…Context specificity could account for the differential regulation of mouse and human TAU by miR‐132 and for the disparate effects on TAU expression observed on miR‐132 genetic knockout or acute knockdown. In contrast, an indirect effect of miR‐132 on TAU phosphorylation has been established more conclusively: miR‐132 expression levels and hyperphosphorylated TAU aggregates inversely correlate in the brain of patients with AD and in AD mouse models (7, 10, 11, 56). This could be possibly explained by up‐regulation of other predicted miR‐132 targets, such as the kinases cyclin‐dependent kinase 5, glycogen synthase kinase 3 b (GSK3B), MAPK1 (ERK2), and MAPK3 (ERK1), all of which have been implicated in aberrant TAU phosphorylation and neurofibrillary tangle formation in AD (58).…”
Section: The Impact Of Mir‐132 Deregulation On Brain Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…However, a deeper understanding of the molecular regulators of AHN, and especially a better understanding of the molecular mechanisms going astray in disease, are a prerequisite for considering restoring AHN as a therapeutic strategy for neurodegenerative diseases. Previously, we and other have shown that miR-132 is strongly and reproducibly downregulated in the hippocampus of AD patients, notably early during disease progression (Hebert et al, 2013; Lau et al, 2013; Patrick et al, 2017; Pichler et al, 2017; Salta and De Strooper, 2017; Salta et al, 2016; Smith et al, 2015; Wong et al, 2013; Zhu et al, 2016). miR-132 overexpression in primary neurons or mouse brain represses pathological hallmarks of AD, such as amyloid plaques, TAU hyperphosphorylation and deposition, and neuronal death (El Fatimy et al, 2018; Hernandez-Rapp et al, 2015; Salta et al, 2016; Smith et al, 2015; Wang et al, 2017; Wong et al, 2013; Zhu et al, 2016) (reviewed in (Salta and De Strooper, 2017)).…”
Section: Introductionmentioning
confidence: 79%
“…This observation is in line with recent reports providing strong evidence for decreased AHN in AD (Moreno-Jiménez et al, 2019; Tobin et al, 2019). Hence, miR-132 deficiency in the hippocampus of AD patients (Hebert et al, 2013; Lau et al, 2013; Patrick et al, 2017; Pichler et al, 2017; Salta and De Strooper, 2017; Salta et al, 2016; Smith et al, 2015; Wong et al, 2013; Zhu et al, 2016) is correlated with the decreased proliferation of neuronal precursors in the dentate gyrus.…”
Section: Resultsmentioning
confidence: 99%